Development of a mathematical model to predict the effect of input parameters on tablet feeding rate of a vibratory bowl feeder - Jain, Anshika; Bansal, Prachi; Khanna, Pradeep (Journal of Production Engineering, 2019)
Rapid industrialization and technological advancements in assembly processes and the demand for feeding the components in assembly lines has grown significantly. It, therefore, becomes essential to optimize the assembly process. Automated or mechanized assembly can be achieved by the use of feeders. This paper describes the mathematical modelling and performance analysis of a vibratory bowl feeder for feeding of medicinal tablets by using design of experiment technique where the adequacy of model was tested by analysis of variance (ANOVA) and significance of regression coefficients is checked by using t-tests. The mathematical model so developed would prove to be useful to establish quantitative relationship between the response parameter and the process parameters like frequency, part population and part size.